Amperometric Trace Determination of As(III), As(V) and Pb(II) with Thioglycolic Acid - Khatkar, S.P.; Boora, Priti (Asian Journal of Chemistry, 2010)
Amperometric trace determination of As(III), As(V) and Pb(II) is reported with the help of thioglycolic acid at d.m.e. 0.1 M NH3 + 0.1 M NH4Cl medium has been employed for As(III), 0.1 M KCl for As(V) and acetate buffer of pH = 4.99 is used for Pb(II). Titration potential has been selected in the limiting region of the anodic wave of thiogycolic acid and metal ion solutions are used as titrant. M : L titrimetric ratios have been found to be 1 : 1 for As(III) and 1 : 2 for As(V) as well as for Pb(II). Solutions as dilute as 18.73 for As(III), 7.49 for As(V) and 20.72 ppm for Pb(II) have been estimated with high degree of accuracy. Interferences of different foreign ions have also been worked out.